A Post-Evaluation Study on the Renewal of Public Space in Qianmen Street of Beijing’s Central Axis Based on Grounded Theory - Shu Tao; Wei Duan (Buildings)
Historic districts are an important component of urban heritage, carrying the memory of the city. The study provides objective spatial level and subjective perception level analysis regarding the evaluation of the renewal of historic districts. We selected Qianmen Street, which is located on the central axis of Beijing, as the research subject. Space syntax was used to determine the importance of the main street to the district, and a kernel density analysis revealed that it was a poor tourist attraction. We used online comment data to establish an evaluation system, based on grounded theory, for the renewal of Qianmen Street. The evaluation system consisted of four primary indicators, including space creation, architectural style conservation, locality, and business management, as well as fifteen secondary indicators. Additionally, an importance–performance analysis (IPA) was used to conduct a quadrant analysis on tourist satisfaction evaluation indicators, in order to analyze influencing factors. The results show that tourists are most concerned about the dimensions of locality and business management, but the level of tourist satisfaction is low. The renewal of the Qianmen historic district should give priority to the creation of its historicity, cultural characteristics, and uniqueness, and should use a small-scale, gradual, and sustainable renewal method.